Tantangan Implementasi Demokrasi Dalam Konteks Negara Konstitusi: Studi Kasus Pada Sistem Hukum Indonesia - Ali Ukasah (Universitas Sains dan Teknologi Komputer, 2024)
The introduction of democracy in the context of a constitutional state is a complex challenge in the context of modern law. This research outlines the crucial challenges faced in efforts to realize democratic principles within the framework of a constitutional state, with a focus on the Indonesian legal system. Through a case study approach, an in-depth analysis is carried out on the implementation of democracy in Indonesia, highlighting the structural, political and cultural problems that influence the process. The research findings illustrate the complexity of the dynamics between democracy and the constitution, as well as the specific challenges that arise in the Indonesian context. The conclusions of this research offer deep insight into the expansion of democratic principles in constitutional states, as well as its practical implications in increasing the maturity of democracy in Indonesia and similar countries.